High temperature resistant coated sand and preparation method thereof

By using a high temperature -resistant agent with a particle size of less than 300 mesh metal oxides in high temperature -resistant membrane sand, and controlling its dispersion, it solves the problem of short temperature resistance and poor heat -resistant heat and high temperature performance. The higher heat -resistant time and lower collapse have improved the quality of the castings.

CN116727597BActive Publication Date: 2025-01-24LIUZHOU LIUJING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310718947.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2025-01-24
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

The existing high-temperature coating sand has a short heat resistance time, poor high-temperature performance, and is prone to combustion at high temperatures, resulting in a reduced collapse and affecting the quality of the casting.

Method used

The high temperature -resistant agent including metal oxides such as magnesium oxide, calcium oxide, chromium oxide, and aluminum oxide is used to control the additional order and response time during the preparation process to control its particle size less than 300 mesh. It is scattered to the interior of the resin.

Benefits of technology

It significantly improves the heat -resistant time and high temperature performance of the coating sand, reduces the amount of gas, reduces the dispersability, and improves the quality and precision of the castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004290467770000111
    Figure BDA0004290467770000111
Patent Text Reader

Abstract

The present invention relates to the technical field of coated sand production, and in particular to a high-temperature resistant coated sand, comprising raw sand, resin, curing agent, lubricant, high-temperature resistant additive and silicone water repellent. Among them, the high-temperature resistant additive is a metal oxide including magnesium oxide, calcium oxide, chromium oxide and aluminum oxide. The present invention also relates to a method for preparing high-temperature resistant coated sand, and the preparation steps are as follows: pour the raw sand into a sand mixer after heating, add a binder, a high-temperature resistant additive, a curing agent and a lubricant respectively in proportion and stir, and after solidification and crushing, add the silicone water repellent again and stir to obtain high-temperature resistant coated sand. The metal oxide used in the present invention as the high-temperature resistant additive of the coated sand will not burn at high temperature, so it will not volatilize gas, thereby reducing the gas emission of the coated sand; at the same time, its particle size is fine, and after adding, it will be partially dispersed into the molten resin after mixing, so that the strength of the finished coated sand is less affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coated sand production, and in particular to high temperature resistant coated sand and a preparation method thereof. Background Art

[0002] Coated sand is molding sand or core sand whose surface is covered with a layer of solid resin film before molding. There are many types of coated sand, including coated sand for centrifugal casting, chilled coated sand, wet coated sand, anti-sticking sand, anti-veining, anti-orange peel coated sand, etc. It is mostly used for steel castings and iron castings, and is also one of the best molding materials for automobiles, tractors, hydraulic parts, etc.

[0003] China's coated sand technology began in the mid-1950s and was discontinued in the 1960s. In the 1980s, due to the rapid development of the automobile industry and the need to export mechanical products, higher requirements were placed on the quality of castings, which promoted the rapid development of coated sand production and application technology. In the early 1990s, coated sand factories across the country developed rapidly, and new products and new technologies continued to emerge. By the 21st century, the annual production and sales volume of my country's coated sand industry had reached more than 900,000 tons, and it was widely used in the production of various complex castings such as automobile cylinder blocks, cylinder heads, intake manifolds, various pipe fittings, pump bodies, etc.

[0004] As a molding material, coated sand has the characteristics of high casting dimensional accuracy and surface finish, good metallographic structure and mechanical properties, low casting scrap rate, thin-walled castings, high production efficiency, and a wide range of castable alloys. It can be said that the performance of coated sand can determine the quality of castings to a certain extent, and directly affect the quality of mechanical products manufactured by it. With the development of industry and social progress, especially the development of the automobile industry, higher requirements are put forward for the quality of castings and the development of the foundry industry. In order to ensure that the quality of castings meets the use requirements, complex thin-walled castings such as automobile engine cylinder blocks, cylinder heads, and container corners need to be cast using high-temperature resistant coated sand during the casting process. The coated sand prepared in the prior art has a certain room temperature tensile strength, but the heat resistance time of the coated sand is short and the high temperature performance is poor. Or it has a decent heat resistance, but it will burn and volatilize a large amount of gas at high temperature, which reduces the disintegration of the coated sand, but affects the performance of the final finished product coated sand, and has a bad effect on the casting. Summary of the invention

[0005] In order to solve the above problems, based on the existing high temperature resistant coated sand and the preparation process of high temperature resistant coated sand, the present invention provides a high temperature resistant coated sand and a preparation method thereof.

[0006] On the one hand, the present invention provides a high temperature resistant coated sand, the raw materials of which are composed of the following raw materials in parts by weight: 1000 parts of raw sand, 20-35 parts of binder, 6-15 parts of curing agent, 1.4-2.5 parts of lubricant, 3-7 parts of high temperature resistant additives, and 1.5-2.5 parts of silicone hydrophobic agent; the high temperature resistant additives are composed of the following metal oxides in parts by weight: 30-70 parts of magnesium oxide, 0-20 parts of calcium oxide, 0-20 parts of chromium oxide, and 0-8 parts of aluminum oxide, and the particle size of the above metal oxides is less than 300 mesh.

[0007] Preferably, the raw materials are composed of the following raw materials in parts by weight: 1000 parts of raw sand, 20-30 parts of binder, 8-12 parts of curing agent, 2-2.3 parts of lubricant, 3-7 parts of high temperature resistant additives, and 1.8-2.0 parts of silicone hydrophobic agent; the high temperature resistant additive is composed of the following metal oxides in parts by weight: 40-60 parts of magnesium oxide, 5-10 parts of calcium oxide, 5-10 parts of chromium oxide, and 2-4 parts of aluminum oxide, and the particle size of the above metal oxides is less than 200 mesh.

[0008] Preferably, the raw sand is selected from one or more of silica sand, quartz sand, gem sand, zircon sand and ceramsite sand.

[0009] Preferably, the binder is a phenolic resin.

[0010] Preferably, the curing agent is a 35% urotropine aqueous solution.

[0011] Preferably, the lubricant is calcium stearate.

[0012] Preferably, the organic silicone water repellent is a liquid organic silicone water repellent.

[0013] On the other hand, the present invention also provides a method for preparing high temperature resistant coated sand, and the preparation steps are as follows:

[0014] (1) Weigh the raw sand, heat it, and pour it into a sand mixer;

[0015] (2) Add a binder and stir, add a high temperature resistant additive and stir, add a curing agent and stir, and add a lubricant and stir;

[0016] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0017] (4) Pour the crushed coated sand into the sand mixer again, add the silicone water repellent, and stir;

[0018] (5) Cooling, screening and packaging.

[0019] Preferably, the heating temperature in step (1) is 130-150°C.

[0020] Preferably, in step (2), the stirring time for adding the binder is 25-40 seconds, the stirring time for adding the high temperature resistant additive is 10-15 seconds, the stirring time for adding the curing agent is 35-55 seconds, and the stirring time for adding the lubricant is 25-55 seconds.

[0021] Preferably, the stirring time in step (4) is 15-25 s, and the speed of the sand mixer is 60-140 r / min.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The high temperature resistant coated sand prepared by the present invention uses metal oxides including magnesium oxide, calcium oxide, chromium oxide and aluminum oxide as high temperature resistant additives to improve the high temperature resistance of the coated sand. Compared with other high temperature resistant additives, the metal oxides of this type of high temperature resistant additive will not burn at high temperatures to produce a large amount of high temperature gas, so the gas emission of the coated sand can be greatly reduced.

[0024] 2. The high temperature resistant coated sand prepared by the present invention adopts a high temperature resistant additive whose metal oxide particle size is less than 300 mesh. Because of its fine particle size, after adding, it can be partially dispersed into the molten resin through crushing, stirring and mixing, thereby reducing the proportion of metal oxide retained on the surface of the coated sand, thereby ensuring its high temperature resistance while having little effect on the strength of the coated sand.

[0025] 3. In a method for preparing high-temperature resistant coated sand of the present invention, by controlling the order of adding raw materials and the reaction time, a high-temperature resistant additive is added after bonding and before curing, so that the metal oxide particles can be better dispersed into the resin during the subsequent crushing, stirring and mixing process, further reducing its influence on the strength of the coated sand. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0027] Example 1

[0028] This embodiment provides a high temperature resistant coated sand, wherein each raw material is prepared according to weight proportion, wherein the raw sand is 1000g of 50 / 100 Inner Mongolia silica sand, the binder is 25g of phenolic resin, the curing agent is 10g of 35% urotropine aqueous solution, the lubricant is 1.5g of calcium stearate, the high temperature resistant additive is 5g, and the liquid silicone hydrophobic agent is 1.5g;

[0029] The high temperature resistant additives are: 50 parts of magnesium oxide, 8 parts of calcium oxide, 8 parts of chromium oxide, and 3 parts of aluminum oxide; the particle size of the above metal oxides is 190 mesh;

[0030] The preparation process is as follows:

[0031] (1) Weigh the raw sand, heat it to 140°C, and pour it into the sand mixer;

[0032] (2) adding a binder, phenolic resin, and stirring for 30 seconds; adding a high temperature resistant additive and stirring for 10 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 40 seconds; and adding a lubricant, calcium stearate, and stirring for 40 seconds;

[0033] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0034] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 20 seconds;

[0035] (5) Cooling, screening and packaging.

[0036] The high temperature resistant coated sand prepared in this embodiment is tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is stably placed on a "concave" type bracket, placed in a high temperature furnace at 1000°C, and its collapse time is measured. The test results are shown in Table 1.

[0037] The high temperature resistant coated sand prepared in this embodiment was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block by Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring). 200 pieces were tested in each group, and the number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0038] Example 2

[0039] This embodiment provides a high temperature resistant coated sand, which is different from the embodiment 1 in that the raw material ratio and the processing time of each process are different. The raw materials are mixed according to weight, including 1000g of 50 / 100 Inner Mongolia silica sand, 30g of binder phenolic resin, 13g of curing agent 35% urotropine aqueous solution; 2.0g of lubricant calcium stearate, 3g of high temperature resistant additive, and 1.9g of liquid silicone hydrophobic agent;

[0040] The high temperature resistant additive is: 60 parts of magnesium oxide, 10 parts of chromium oxide, and 5 parts of aluminum oxide; the particle size of the above metal oxides is 280 mesh;

[0041] The preparation process is as follows:

[0042] (1) Weigh the raw sand, heat it to 145°C, and pour it into the sand mixer;

[0043] (2) adding a binder, phenolic resin, and stirring for 35 seconds; adding a high temperature resistant additive and stirring for 15 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 50 seconds; and adding a lubricant, calcium stearate, and stirring for 30 seconds;

[0044] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0045] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 25 seconds;

[0046] (5) Cooling, screening and packaging.

[0047] The high temperature resistant coated sand prepared in this embodiment is tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is stably placed on a "concave" type bracket, placed in a high temperature furnace at 1000°C, and its collapse time is measured. The test results are shown in Table 1.

[0048] The high temperature resistant coated sand prepared in this embodiment was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block by Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring). 200 pieces were tested in each group, and the number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0049] Example 3

[0050] This embodiment provides a high temperature resistant coated sand, which is different from the embodiment 1 in that the raw material ratio and the processing time of each process are different. The raw materials are mixed according to weight, including 1000g of 50 / 100 Inner Mongolia silica sand, 20g of binder phenolic resin, 9g of curing agent 35% urotropine aqueous solution; 1.4g of lubricant calcium stearate, 6g of high temperature resistant additive, and 2.5g of liquid silicone hydrophobic agent;

[0051] The high temperature resistant additive is: 70 parts of magnesium oxide, 10 parts of calcium oxide, and 2 parts of aluminum oxide; the particle size of the above metal oxides is 250 mesh;

[0052] The preparation process is as follows:

[0053] (1) Weigh the raw sand, heat it to 130°C, and pour it into the sand mixer;

[0054] (2) adding a binder, phenolic resin, and stirring for 30 seconds; adding a high temperature resistant additive and stirring for 10 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 40 seconds; and adding a lubricant, calcium stearate, and stirring for 25 seconds;

[0055] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0056] (4) Pour the crushed coated sand into the sand mixer again, add liquid silicone water repellent, and stir for 15 seconds;

[0057] (5) Cooling, screening and packaging.

[0058] The high temperature resistant coated sand prepared in this embodiment is tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is stably placed on a "concave" type bracket, placed in a high temperature furnace at 1000°C, and its collapse time is measured. The test results are shown in Table 1.

[0059] The high temperature resistant coated sand prepared in this embodiment was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block by Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring). 200 pieces were tested in each group, and the number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0060] Example 4

[0061] This embodiment provides a high temperature resistant coated sand, which is different from the embodiment 1 in that the raw material ratio and the processing time of each process are different. The raw materials are mixed according to weight, including 1000g of 50 / 100 Inner Mongolia silica sand, 35g of binder phenolic resin, 14g of curing agent 35% urotropine aqueous solution; 2.5g of lubricant calcium stearate, 7g of high temperature resistant additive, and 2.3g of liquid silicone hydrophobic agent;

[0062] The high temperature resistant additive is: 40 parts of magnesium oxide and 2 parts of chromium oxide; the particle size of the above metal oxide is 210 mesh;

[0063] The preparation process is as follows:

[0064] (1) Weigh the raw sand, heat it to 150°C, and pour it into the sand mixer;

[0065] (2) adding a binder, phenolic resin, and stirring for 35 seconds; adding a high temperature resistant additive and stirring for 12 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 55 seconds; and adding a lubricant, calcium stearate, and stirring for 55 seconds;

[0066] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0067] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 25 seconds;

[0068] (5) Cooling, screening and packaging.

[0069] The high temperature resistant coated sand prepared in this embodiment is tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is stably placed on a "concave" type bracket, placed in a high temperature furnace at 1000°C, and its collapse time is measured. The test results are shown in Table 1.

[0070] The high temperature resistant coated sand prepared in this embodiment was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block by Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring). 200 pieces were tested in each group, and the number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0071] Example 5

[0072] This embodiment provides a high temperature resistant coated sand, which is different from the embodiment 1 in that the raw material ratio and the processing time of each process are different. The raw materials are mixed according to weight, including 1000g of 50 / 100 Inner Mongolia silica sand, 20g of binder phenolic resin, 9g of curing agent 35% urotropine aqueous solution; 1.4g of lubricant calcium stearate, 4g of high temperature resistant additive, and 1.8g of liquid silicone hydrophobic agent;

[0073] The high temperature resistant additive is: 70 parts of magnesium oxide; the particle size of the above metal oxide is 150 mesh;

[0074] The preparation process is as follows:

[0075] (1) Weigh the raw sand, heat it to 130°C, and pour it into the sand mixer;

[0076] (2) adding a binder, phenolic resin, and stirring for 30 seconds; adding a high temperature resistant additive and stirring for 10 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 40 seconds; and adding a lubricant, calcium stearate, and stirring for 25 seconds;

[0077] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0078] (4) Pour the crushed coated sand into the sand mixer again, add liquid silicone water repellent, and stir for 15 seconds;

[0079] (5) Cooling, screening and packaging.

[0080] The high temperature resistant coated sand prepared in this embodiment is tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is stably placed on a "concave" type bracket, placed in a high temperature furnace at 1000°C, and its collapse time is measured. The test results are shown in Table 1.

[0081] The high temperature resistant coated sand prepared in this embodiment was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block by Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring). 200 pieces were tested in each group, and the number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0082] Comparative Example 1

[0083] This comparative example provides a coated sand, which is mainly different from Example 1 in that the raw materials in this example do not include a high temperature resistant additive. The raw materials in this example include 1000g of raw sand 50 / 100 Inner Mongolia silica sand, 25g of a binder phenolic resin, 14g of a curing agent 35% urotropine aqueous solution, 1.9g of a lubricant calcium stearate, and 1.5g of a liquid organic silicon hydrophobic agent;

[0084] The preparation process is as follows:

[0085] (1) Weigh the raw sand, heat it to 140°C, and pour it into the sand mixer;

[0086] (2) adding a binder, phenolic resin, and stirring for 30 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 40 seconds; and adding a lubricant, calcium stearate, and stirring for 40 seconds;

[0087] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0088] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 20 seconds;

[0089] (5) Cooling, screening and packaging.

[0090] The high temperature resistant coated sand prepared in this comparative example was tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is placed steadily on the "concave" type bracket, put into a high temperature furnace at 1000℃, and its collapse time is measured. The test results are shown in Table 1.

[0091] The high temperature resistant coated sand prepared in this comparative example was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block of Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring), and 200 pieces were tested in each group. The number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0092] Comparative Example 2

[0093] This comparative example provides a coated sand, which is mainly different from Example 1 in that the amount of high temperature resistant additive added in this example is too small. The raw materials of this comparative example include: 1000g of raw sand 50 / 100 Inner Mongolia silica sand, 25g of binder phenolic resin, 14g of curing agent 35% urotropine aqueous solution; 1.5g of lubricant calcium stearate, 1g of high temperature resistant additive, and 1.5g of liquid silicone hydrophobic agent;

[0094] The high temperature resistant additives are: 50 parts of magnesium oxide, 8 parts of calcium oxide, 8 parts of chromium oxide, and 3 parts of aluminum oxide; the particle size of the above metal oxides is 190 mesh;

[0095] The preparation process is as follows:

[0096] (1) Weigh the raw sand, heat it to 140°C, and pour it into the sand mixer;

[0097] (2) adding a binder, phenolic resin, and stirring for 30 seconds; adding a high temperature resistant additive and stirring for 10 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 40 seconds; and adding a lubricant, calcium stearate, and stirring for 40 seconds;

[0098] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0099] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 20 seconds;

[0100] (5) Cooling, screening and packaging.

[0101] The high temperature resistant coated sand prepared in this comparative example was tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is placed steadily on the "concave" type bracket, put into a high temperature furnace at 1000℃, and its collapse time is measured. The test results are shown in Table 1.

[0102] The high temperature resistant coated sand prepared in this comparative example was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block of Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring), and 200 pieces were tested in each group. The number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0103] Comparative Example 3

[0104] This comparative example provides a coated sand, which is mainly different from Example 1 in that the amount of high temperature resistant additive added in this example is too much. The raw materials of this comparative example include: 1000g of raw sand 50 / 100 Inner Mongolia silica sand, 25g of binder phenolic resin, 14g of curing agent 35% urotropine aqueous solution; 1.9g of lubricant calcium stearate, 10g of high temperature resistant additive, and 1.5g of liquid silicone hydrophobic agent;

[0105] The high temperature resistant additives are: 50 parts of magnesium oxide, 8 parts of calcium oxide, 8 parts of chromium oxide, and 3 parts of aluminum oxide; the particle size of the above metal oxides is 190 mesh;

[0106] The preparation process is as follows:

[0107] (1) Weigh the raw sand, heat it to 140°C, and pour it into the sand mixer;

[0108] (2) adding a binder, phenolic resin, and stirring for 30 seconds; adding a high temperature resistant additive and stirring for 10 seconds; adding a curing agent, 35% urotropine aqueous solution, and stirring for 40 seconds; and adding a lubricant, calcium stearate, and stirring for 40 seconds;

[0109] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0110] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 20 seconds;

[0111] (5) Cooling, screening and packaging.

[0112] The high temperature resistant coated sand prepared in this comparative example was tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is placed steadily on the "concave" type bracket, put into a high temperature furnace at 1000℃, and its collapse time is measured. The test results are shown in Table 1.

[0113] The high temperature resistant coated sand prepared in this comparative example was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block of Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring), and 200 pieces were tested in each group. The number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0114] Comparative Example 4

[0115] This comparative example provides a coated sand, which is mainly different from Example 1 in that the particle size of the metal oxide in the high temperature resistant additive used in this example is relatively large. The raw materials of this comparative example include: 1000g of raw sand 50 / 100 Inner Mongolia silica sand, 25g of binder phenolic resin, 15g of curing agent 35% urotropine aqueous solution; 1.5g of lubricant calcium stearate, 5g of high temperature resistant additive, and 1.5g of liquid silicone hydrophobic agent;

[0116] The high temperature resistant additive is: 50 parts of magnesium oxide, 8 parts of calcium oxide, 8 parts of chromium oxide, and 3 parts of aluminum oxide; the particle size of the above metal oxides is 400 mesh;

[0117] The preparation process is as follows:

[0118] (1) Weigh the raw sand, heat it to 140°C, and pour it into the sand mixer;

[0119] (2) adding a binder phenolic resin and stirring for 30 seconds, adding a curing agent 35% urotropine aqueous solution and stirring for 40 seconds, adding a lubricant calcium stearate and stirring for 40 seconds, and adding a high temperature resistant additive and stirring for 10 seconds;

[0120] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0121] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 20 seconds;

[0122] (5) Cooling, screening and packaging.

[0123] The high temperature resistant coated sand prepared in this comparative example was tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is placed steadily on the "concave" type bracket, put into a high temperature furnace at 1000℃, and its collapse time is measured. The test results are shown in Table 1.

[0124] The high temperature resistant coated sand prepared in this comparative example was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block of Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring), and 200 pieces were tested in each group. The number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0125] Comparative Example 5

[0126] This comparative example provides a coated sand, which is mainly different from Example 1 in that the high temperature resistant additive is added last in the preparation steps of this example. The raw materials of this comparative example include: 1000g of raw sand 50 / 100 Inner Mongolia silica sand, 25g of binder phenolic resin, 10g of curing agent 35% urotropine aqueous solution; 1.5g of lubricant calcium stearate, 5g of high temperature resistant additive, and 1.5g of liquid silicone hydrophobic agent;

[0127] The high temperature resistant additives are: 50 parts of magnesium oxide, 8 parts of calcium oxide, 8 parts of chromium oxide, and 3 parts of aluminum oxide; the particle size of the above metal oxides is 190 mesh;

[0128] The preparation process is as follows:

[0129] (1) Weigh the raw sand, heat it to 140°C, and pour it into the sand mixer;

[0130] (2) adding a binder phenolic resin and stirring for 30 seconds, adding a curing agent 35% urotropine aqueous solution and stirring for 40 seconds, adding a lubricant calcium stearate and stirring for 40 seconds, and adding a high temperature resistant additive and stirring for 10 seconds;

[0131] (3) pouring the solidified coated sand into a crushing screen for crushing;

[0132] (4) Pour the crushed coated sand back into the sand mixer, add liquid silicone water repellent, and stir for 20 seconds;

[0133] (5) Cooling, screening and packaging.

[0134] The high temperature resistant coated sand prepared in this comparative example was tested for room temperature tensile strength, room temperature compressive strength, ignition loss, gas evolution, and hot tensile strength of the coated sand according to GB / T8583-2008 standard. The heat resistance time test method is: the prepared "I" type sample is placed steadily on the "concave" type bracket, put into a high temperature furnace at 1000℃, and its collapse time is measured. The test results are shown in Table 1.

[0135] The high temperature resistant coated sand prepared in this comparative example was tested using the above ultra-high temperature resistant coated sand in the casting of B15 cylinder block of Liuzhou Liuji Wuling Power Co., Ltd. In order to test the high temperature resistance, the pouring temperatures were 1450°C, 1550°C, 1650°C and 1700°C respectively (the above pouring was insulation pouring), and 200 pieces were tested in each group. The number of sand sticking defects and the number of scraps were counted. The test results are shown in Table 2.

[0136] Table 1 Performance test results of each coated sand

[0137]

[0138] Table 2 Test results of the number of rejects of each coated sand at different pouring temperatures

[0139] 1450℃ scrap number 1550℃ scrap number 1650℃ scrap number 1700℃ scrap number Example 1 1 0 1 2 Example 2 1 1 1 5 Example 3 2 1 5 6 Example 4 1 2 8 4 Example 5 1 1 6 7 Comparative Example 1 2 4 82 198 Comparative Example 2 1 8 63 178 Comparative Example 3 1 10 72 167 Comparative Example 4 1 20 90 196 Comparative Example 5 2 23 89 193

[0140] As can be seen from Table 1 and Table 2, the high temperature resistant coated sand of the present invention adds metal oxides including magnesium oxide, calcium oxide, chromium oxide and aluminum oxide with smaller particle size as high temperature resistant additives during the preparation process, so that the room temperature tensile strength of the prepared coated sand is ≥4.0Mp, the loss on ignition is ≤4.0%, the gas evolution is ≤22mL / g, the hot tensile strength is ≥2.0Mpa, the heat resistance time is ≥135s, and the number of waste products of the coated sand is low when cast at 1550-1700℃. The room temperature tensile strength and hot tensile strength of the coated sand prepared by the present invention are both high, the heat resistance time is long and the gas evolution is low, making it more suitable for improving the quality of precision castings.

[0141] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A high temperature resistant coated sand, characterized in that: It is composed of the following raw materials in parts by weight: 1000 parts of raw sand, 20-35 parts of binder, 6-15 parts of curing agent, 1.4-2.5 parts of lubricant, 3-7 parts of high temperature resistant additive, and 1.5-2.5 parts of organic silicon water repellent; The high temperature resistant additive is composed of the following metal oxides in parts by weight: 30-70 parts of magnesium oxide, 0-20 parts of calcium oxide, 0-20 parts of chromium oxide, and 0-8 parts of aluminum oxide; The particle size of the metal oxide is less than 300 mesh; The method for preparing the high temperature resistant coated sand comprises the following steps: (1) Weigh the raw sand, heat it, and pour it into a sand mixer; (2) Add a binder and stir, add a high temperature resistant additive and stir, add a curing agent and stir, and add a lubricant and stir; (3) pouring the solidified coated sand into a crushing screen for crushing; (4) Pour the crushed coated sand into the sand mixer again, add the silicone water repellent, and stir; (5) Cooling, screening and packaging.

2. The high temperature resistant coated sand according to claim 1, characterized in that: The raw sand is selected from one or more of silica sand, quartz sand, gem sand, zircon sand and ceramsite sand.

3. The high temperature resistant coated sand according to claim 1, characterized in that: The binder is phenolic resin.

4. The high temperature resistant coated sand according to claim 1, characterized in that: The curing agent is a 35% urotropine aqueous solution.

5. The high temperature resistant coated sand according to claim 1, characterized in that: The lubricant is calcium stearate.

6. The high temperature resistant coated sand according to claim 1, characterized in that: The organic silicon water repellent is a liquid organic silicon water repellent.

7. The high temperature resistant coated sand according to claim 1, characterized in that: The heating temperature in step (1) is 130-150°C.

8. The high temperature resistant coated sand according to claim 1, characterized in that: In step (2), the stirring time for adding the binder is 25-40 seconds, the stirring time for adding the high temperature resistant additive is 10-15 seconds, the stirring time for adding the curing agent is 35-55 seconds, and the stirring time for adding the lubricant is 25-55 seconds.

9. The high temperature resistant coated sand according to claim 1, characterized in that: The stirring time in step (4) is 15-25s, and the rotating speed of the sand mixer is 60-140r / min.

Citation Information

Patent Citations

  • Coating sand for three-dimensional printing and preparation method of coating sand

    CN109746382A

  • Moisture-proof and anti-caking precoated sand and preparation method thereof

    CN115555512A